KEMAMPUAN KOMUNIKASI MATEMATIS MAHASISWA CALON GURU DALAM MENYELESAIKAN MASALAH MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN - Sayang, Arien; Laurens, Theresia; Palinussa, Anderson L (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2019)
This study aims to describe the mathematical communication skills of prospective teacher students in solving mathematical problems Evaluated from Personality Types (artisan, idealist, guardian, dan rational). This research is a kind of qualitative exploratory research. The subjects used in this study were students of the 4th semester Mathematics Education consisting of 1 student for each type of artisan personality (SA), idealist personality (SI), guardian personality (SG), and rational personality (SR). The selection of research subjects is based on stratified sampling technique then purposive sampling. Data analysis techniques refer to the concept of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The data validity technique uses the method triangulation and source triangulation. The results of the research show that: 1) SA meets three indicators namely being able to write information that is known and asked, draw pictures, and do calculations; 2) SI fulfills four indicators which are able to write information that is known and asked, draw pictures, do calculations, and apply mathematical symbols and rules in accordance with the intended problem; 3) SG fulfills three indicators namely being able to make drawings, do calculations, and write symbols and mathematical rules; 4) SR fulfills two indicators namely being able to write information that is known and asked, and doing calculations.